A STUDY OF ORGANIZATIONAL PERFORMANCE OF WOMEN ENTREPRENEURS IN NORTHERN DISTRICT - Pushpanathan, A.; Nimalathasan, B.; Subathini, R. (My University, 2013)
The main objective of the study is to analysis the women entrepreneurs in Northern District and their organizational performance. Secondary literature reviews and primary data collections methods were used to conduct the study effectively. Random sampling method was adopted to select the respondents. The structural equation model was used in this study as well. The results revealed that the sole proprietorship performed very well (59.1 percent) than the family business and partnership. The food items have higher mean value in the profitability, turnover and customer choice than the other products. The paper product has higher mean value in the investment than other products. And pottery product has higher mean value in seasonal sales than other products. Finally customer satisfaction was discussed in this study. The insignificant effect was observed among the customer choice, investment, and seasonal purchase, and customer satisfaction.
Keywords: Organizational Performance; Women Entrepreneurs